2005
DOI: 10.1152/ajpheart.00646.2004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age and hyperglycemia on the mechanical behavior of intact human coronary arteries: an ex vivo intravascular ultrasound study

Abstract: Despite their advantages, percutaneous coronary interventional procedures are less effective in diabetic patients. Changes in the mechanical properties of vascular walls secondary to long-term hyperglycemia as well as other factors such as age may influence coronary distensibility. This investigation is aimed at deciphering the extent of these effects on distensibility of postmortem human coronary arteries in a controlled manner. Excised human left anterior descending (LAD) coronary arteries were obtained with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
10
1
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 33 publications
7
10
1
4
Order By: Relevance
“…Maybe the most complete in-vitro work has been carried out by Ozolanta et al [12]; they studied in 205 patients the evolution with age of distensibility and modulus of elasticity of coronary arteries in the 0-240 mmHg pressure range. Similar research was performed by Williams et al [10] (in-vivo) and Tajaddini et al [11] (in-vitro), which showed -in agreement with Ozolanta et al [12]-that distensibility decreases and the modulus of elasticity increases with age. To the authors' knowledge, most of the mechanical studies on human coronary arteries in the literature have been limited to compliance and stiffness measurements not beyond twice or three times physiological pressure.…”
Section: Introductionsupporting
confidence: 88%
“…Maybe the most complete in-vitro work has been carried out by Ozolanta et al [12]; they studied in 205 patients the evolution with age of distensibility and modulus of elasticity of coronary arteries in the 0-240 mmHg pressure range. Similar research was performed by Williams et al [10] (in-vivo) and Tajaddini et al [11] (in-vitro), which showed -in agreement with Ozolanta et al [12]-that distensibility decreases and the modulus of elasticity increases with age. To the authors' knowledge, most of the mechanical studies on human coronary arteries in the literature have been limited to compliance and stiffness measurements not beyond twice or three times physiological pressure.…”
Section: Introductionsupporting
confidence: 88%
“…Maybe the most complete in-vitro work has been carried out by Ozolanta et al [12]; they studied in 205 patients the evolution with age of distensibility and modulus of elasticity of coronary arteries in the 0-240 mmHg pressure range. Similar research was performed by Williams et al [10] (in-vivo) and Tajaddini et al [11] (in-vitro), which showed -in agreement with Ozolanta et al [12]-that distensibility decreases and the modulus of elasticity increases with age.…”
Section: Introductionsupporting
confidence: 88%
“…The biomechanical properties of these SMC microintegrated tubes were assessed and found to be strong and flexible with compliances, stiffness, and burst strengths appropriate for blood vessel replacement. Values can be compared with those of Tajaddini et al who recently provided a thorough mechanical characterization of human coronary arteries, [30] which represent the main targets for future clinical applications of smalldiameter engineered vessels. According to those published data the microintegrated tubular constructs appear to have very similar mechanical properties to those of healthy coronary arteries (compliance = 14.1 ± 5.9 × 10 −4 mmHg, stiffness index = 16.9 ± 7.1, elastic modulus = 1.41 ± 0.72 MPa).…”
Section: Discussionmentioning
confidence: 99%